2023
DOI: 10.1007/s12026-023-09362-8
|View full text |Cite
|
Sign up to set email alerts
|

Human antibody profiling technologies for autoimmune disease

Abstract: Autoimmune diseases are caused by the break-down in self-tolerance mechanisms and can result in the generation of autoantibodies specific to human antigens. Human autoantigen profiling technologies such as solid surface arrays and display technologies are powerful high-throughput technologies utilised to discover and map novel autoantigens associated with disease. This review compares human autoantigen profiling technologies including the application of these approaches in chronic and post-infectious autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“… 5 In addition, some studies reported heterogeneity among individuals in the autoantibody binding sites and their effect. 28 , 29 The role of EPO-EPOR in the pathophysiology of anemia may differ by ethnicity. Because the proportion of participants from Japan was small in the CREDENCE trial, this may explain potential differences with earlier studies, which were exclusively performed in Japanese participants.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In addition, some studies reported heterogeneity among individuals in the autoantibody binding sites and their effect. 28 , 29 The role of EPO-EPOR in the pathophysiology of anemia may differ by ethnicity. Because the proportion of participants from Japan was small in the CREDENCE trial, this may explain potential differences with earlier studies, which were exclusively performed in Japanese participants.…”
Section: Discussionmentioning
confidence: 99%
“…Следует подчеркнуть инновационные «аутоантигеномные» методы, которые в последние годы все шире используются для определения аутоантител при САРЗ и COVID-19, позволяющие выявлять аутоантитела к ранее не известным аутоантигенам, и при заболеваниях, которые ранее не рассматривались как аутоиммунные, имеют методические ограничения (характер гликозилирования аутоантител и пост трансляционной модификации аутоантигенов и др.) [312] и нуждаются в стандартизации и валидации [313][314][315]. Дос тупные для клинической практики методы, позволяющие дифференцировать «патогенные» от «защитных» аутоантител, охарактеризовать их субкласс, аллотип, гликозилирование [316,317] и, что самое важное, их функциональную активность, не разработаны.…”
Section: перспективыunclassified
“…Advanced high-profile techniques, such as solid surface arrays and display technologies,16 have been boosting the biomarker discovery. Despite considerable progress and widespread application in autoantibody discovery,17–19 the utility of high-throughput assays, particularly protein microarrays, remains restricted by the limited amount of miniaturised test sites.…”
Section: Introductionmentioning
confidence: 99%